Vegetative propagation of adult Ilex paraguariensis trees through epicormic shoots - doi: 10.4025/actasciagron.v35i1.15958 (Acta Scientiarum. Agronomy, 2012)
The difficulty and length of time required for seed germination of mate (Ilex paraguariensis), as well as the pressing need for clonal multiplication of improved genetic material, has resulted in several studies related to vegetative propagation in an effort to obtain rooted cuttings more quickly and with better genetic quality. Currently, the biggest challenge is propagating and rooting adult plants selected in the field without requiring clear cutting to generate conditions for the basal induction of juvenile sprouts. Therefore, the objective of this study was to develop a method to rescue adult mate plants through the generation of epicormic sprouts. To accomplish this, tree branches of mate that were at least 19 years of age were collected and packed in trays with sand for sprouting. Different solutions containing a mixture of sucrose and indole-3-butyric acid (IBA) were sprayed in branches at 29, 22, 15, 8 and 1 day(s) before collection. We conclude that the vegetative propagation of adult mate trees is technically efficient and requires no treatment with sucrose or IBA and results in the formation of plants suitable for planting or serving as mother plants for continuous multiplication via cloning.